Structural and Thermal Properties of Ethiopian Eri and Mulberry Silk Fibres. (31st October 2020) - Melesse, Getnet; Atalie, Desalegn; Koyrita, Ayano
Abstract : Silk fibre has received attention in the biomedical sector rather than textile production because of its excellent biocompatibility properties in the past century. Although silk fibre properties are different from area to area, it has created an opportunity in the biomedical sector to develop new silk-based medical textile products. This research work aimed to study the structural, physical, mechanical, and thermal properties of Ethiopian silkworm cocoon's filament. Eri and mulberry silk fibre properties such as morphological structure, chemical properties, linear density, filament length, tensile strength, elongation, thermal property, and luster were measured using ES ISO and ASTM standard methods. Statistical analysis result showed that eri silk fibre from Arba Minch had water removal temperature between 100°C and 125°C with a degradation temperature of around 400°C and eri silk fibre from both Addis Ababa and Awassa had an almost similar water removal temperature around 100°C and degradation temperature around 420°C. Tensile strength and elongation of both eri and mulberry silk fibres had significant differences among each region. The highest tensile strength of 4.47 cN was observed from Addis Ababa, and the highest elongation of 20.01% was found from the Arba Minch eri silk fibre. The coarser linear density of 2.496 dtex from Arba Minch and finer count of 2.392 dtex were exhibited from Awassa. Arba Minch eri silk fibre had the highest filament length of 403.04 m and the least fibre length of 399.2 m recorded at Addis Ababa, and a better whiteness (Rd) value of 58.21 was observed at Arba Minch eri silk fibre. Bivoltine and multivoltine mulberry silk fibres had an average tensile strength of 8.01 and 11.83 cN, elongation of 10.3 and 12.1%, fineness of 3.2 and 3.16 dtex, and filament length of 1208.6 and 1028.26 m, respectively, in the same place of Arba Minch. The morphological structure of eri silk fibre from each region had an almost smooth and clean surface, but bivoltine and multivoltine mulberry silk fibres were somehow rough and had spots. According to the comparison results, Ethiopian silk fibres can be utilised more in the biomedical application and competitive in the global market.